Environmental degradation in terms of health expenditure, education and economic growth. Evidence of novel approach - Bu, Junqin; Ali, Kishwar (Frontiers in Environmental Science, 2022)
Eco-sustainable activities are particularly essential in the modern era to slow the rate of environmental degradation and its adverse consequences. Increased physical education has a good impact on our health and has the ability to reduce environmental deterioration. Therefore, the present study examined the effects of health expenditure, economic growth, education and population on environmental degradation in seven emerging economies from 2000 to 2019. The Cross-Section Dependency (CSD) reflected the panel nations' CSD, whereas the CIPS and CADF tests confirmed all indicators' stationarity at first difference. Thus, the Westerlund cointegration approach identified a long-term relationship between the indicators. The long-run estimation PFMOLS and PDOLS found that education helps mitigate CO2 emissions and increase environmental quality in E-7. Conversely, health expenditure, economic growth, and population increase CO2 emissions and decrease environmental quality. Moreover, the outcomes of PFMOLS and PDOLS are authenticated by AMG and CCEMG assessments. The study suggests adopting physical education and physical health activities to curb environmental degradation in the panel region.